2021
DOI: 10.1021/acs.orglett.1c00493
|View full text |Cite
|
Sign up to set email alerts
|

α-Oxocarboxylic Acids as Three-Carbon Insertion Units for Palladium-Catalyzed Decarboxylative Cascade Synthesis of Diverse Fused Heteropolycycles

Abstract: A novel palladium-catalyzed decarboxylative cascade cyclization for the assembly of diverse fused heteropolycycles by employing α-oxocarboxylic acids as three-carbon insertion units is reported. This protocol enables the synthesis of isoquinolinedione-and indolo[2,1-a]isoquinolinone-fused benzocycloheptanones in moderate to good yields by the use of different aryl iodides, including alkene-tethered 2-iodobenzamides and 2-(2-iodophenyl)-1H-indoles. Notably, the approach achieves simultaneous construction of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…On the basis of the above results and previous reports, , a possible mechanistic pathway for this transformation was outlined in Scheme . Initially, the catalytic cycle starts with the oxidative addition of Pd(0) to the C–I bond to form aryl–Pd­(II) intermediate A , which preferentially undergoes an intramolecular Heck cyclization and generates a primary alkylpalladium species B .…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…On the basis of the above results and previous reports, , a possible mechanistic pathway for this transformation was outlined in Scheme . Initially, the catalytic cycle starts with the oxidative addition of Pd(0) to the C–I bond to form aryl–Pd­(II) intermediate A , which preferentially undergoes an intramolecular Heck cyclization and generates a primary alkylpalladium species B .…”
mentioning
confidence: 56%
“…16f,j However, to the best of our knowledge, a transition-metal-catalyzed cascade C−H functionalization of indole-containing alkene-tethered aryl halides with alkynes has not been developed. Inspired by the above reports and our interest in palladium catalyzed cascade chemistry, 17 we assume that the internal alkyne can be incorporated as an effective C2 synthon into a five-membered palladacycle intermediate, which may be easily formed from an indole-containing alkene-tethered aryl halide through a sequential intramolecular carbopalladation and C−H activation process, resulting in a series of fused polycyclic skeletons 18 We began our study by investigating the reaction with 1…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, our group and others designed various halogenated carboxylic acids as C1, C2 or C3 insertion units to construct different size-ring fused cyclic compounds via this strategy. [53][54][55][56][57][58][59][60][61][62] In these reactions, it was observed that the inser- tion of carboxylic acids usually showed good regioselectivity. Thus, the methods used o-halobenzoic acids, arynes and aryl halides as aromatic ring precursors, which could be complementary.…”
Section: Palladium-catalysed Intermolecular C-h Annulation Of Aryl Ha...mentioning
confidence: 99%
“…The alkylpalladium II species can cleave C-H bonds of an aryl group tethered to the alkene moiety to generate C,C-palladacycles. The palladacycles may undergo intramolecular cyclization [24][25][26][27][28][29][30][31][32][33][34][35] or be captured with external reagents [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. These types of reactions not only represent a novel strategy to activate C-H bonds that are not in proximity to directing groups, but also provide easy access to complex polycyclic compounds.…”
Section: Introductionmentioning
confidence: 99%